IL-35 polymorphisms and cognitive decline did not show any association in patients with coronary heart disease over a 2-year period: A retrospective observational study (STROBE compliant). Issue 31 (31st July 2020) - Shi, Ying; Zhang, Shu; Xue, Yan; Yang, Zicong; Lin, Yingzhong; Liu, Ling; Liu, Hairun
Abstract : Abstract: Prior evidence suggested that inflammation and inflammatory cytokines polymorphisms might be essential in the development of coronary heart disease (CHD) and cognitive decline. The following study investigated the associations between interleukin-35 ( IL-35) polymorphisms and cognitive decline in CHD patients over a 2-year period. CHD patients were enrolled between January 2015 and January 2016. Cognitive function, including memory, orientation, verbal and attention were assessed using Telephone Interview for Cognitive Status-Modified (TICS-m) during a 2-year follow-up. Genotypes of the single nucleotide polymorphisms (SNPs), including rs2243115, rs568408, rs582054, rs583911, rs428253, rs4740 and rs393581 of IL-35 were examined by MassArray (Sequenom). The differences of TICS-m score between 2-year interval were used to estimate the cognitive decline; linear regression model was used to analyze the association between IL-35 polymorphisms and cognitive decline in CHD patients after a 2-year follow-up. The mean age of study individuals was 60.58 (±7.86) years old. There were 255 (68.5%) males and 117 (31.5%) female patients. The TICS-m scores, including overall cognition score, verbal attention and memory scores gradually decreased over a 2 year follow up period ( P < .001, respectively), whereas there was no difference in orientation function score between the 1-year and 2-year follow-up ( P = .448). Furthermore, after adjusting for age, sex, history of hypertension(HT) and Diabetes mellitus(DM), smoking, education, Therapy regimen (PCI, CABG, medication) left ventricular ejection fraction (LVEF), and the severity of coronary artery stenosis (Gensini score), no association was found between IL-35 rs2243115, rs568408, rs582054, rs583911, rs428253, rs4740 genotypes and cognitive decline in CHD patients over a 2-year period. Our data reveled that IL-35 polymorphisms was not associated with cognitive decline in CHD patients over a 2-year period. Yet, further studies are needed to confirm the role of cytokine gene polymorphisms in cognitive decline among CHD patients. Abstract : Supplemental Digital Content is available in the text